Antral plexiform fibromyxoma: case report of a rare mesenchymal neoplasm - Oliveira dos Santos, Carlos Eduardo (2023)
Plexiform fibromyxoma (PF) is a rare mesenchymal neoplasm of the stomach usually arising in the gastric antrum, and its main differential diagnosis is gastrointestinal stromal tumor. Most common symptoms are hematemesis, anemia. Immunohistochemically, positivity for smooth muscle actin (SMA) and vimentin suggests the diagnosis of PF. We report the case of a 56-year-old female patient with a 30- day history of nausea at presentation 4 years ago. Gastroscopy at that time revealed a subepithelial lesion (SEL) in the gastric antrum, measuring approximately 20 mm in diameter, with leakage of serous fluid after biopsy. Histopathology showed only an inflammatory process. Follow-up gastroscopies were performed 24, 36, and 48 months later, with surveillance biopsy at each follow-up. The last gastroscopies showed changes in lesion appearance, reduction in size, and absence of fluid leakage. Histopathology showed bland spindle cell proliferation, with a vaguely plexiform/multinodular pattern, in a fibromyxoid stroma with an arborizing capillary network without mitoses. The tumor cells were positive for SMA and negative for DOG1, CD117, CD34, S100, desmin, EMA, CD10, calponin, and beta-catenin. The choice of treatment and follow-up depends on the SEL features, but because no cases of malignancy or metastatic disease have previously been reported, the patient chose a conservative approach.